PENGARUH TEKNIK RELAKSASI NAFAS DALAM TERHADAP PENURUNAN TINGKAT NYERI PADA PASIEN POST OPERATIVE FRAKTU: THE EFFECT OF DEEP BREATHING RELAXATION TECHNIQUES ON REDUCING PAIN LEVELS IN FRACTUOUS POST OPERATIVE PATIENTS - Kusyani, Asri; Aziz, Aditya Nuraminudin; Vidhiastutik, Yusiana (WELL BEING, 2024)
Introduction:Pain management is one of the methods used in the health field to deal with the pain experienced by patients. Relaxation techniques are a non-drug alternative in pain management strategies. The aim of the research was to determine the effect of deep breathing relaxation techniques on reducing pain levels in post-operative fracture patients. The research design uses a quasi-experiment with a one group pretest-posttest design. The population in this study was 36 patients and the research sample consisted of 18 respondents using an accidental sampling technique according to the inclusion criteria for post-operative fracture patients. The variables in this study were deep breathing relaxation and pain scores for post-fracture surgery patients. Data analysis used the Wilcoxon statistical test with a significant value of p<0.05. The results of the Wilcoxon statistical test analysis of the attitude variable showed p = 0.001, so H1 was accepted. : research shows that before being given deep breathing relaxation therapy 9 (50%) respondents had severe pain scores and after being given deep breathing therapy the majority of 15 (83%) respondents had moderate pain scores. There is an influence of deep breathing relaxation techniques on reducing pain levels in post-operative fracture patient